2016
DOI: 10.1086/685079
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Function of miR‐214 in Pulmonary Arterial Hypertension

Abstract: Dysregulation of microRNAs (miRNAs) can contribute to the etiology of diseases, including pulmonary arterial hypertension (PAH). Here we investigated a potential role for the miR-214 stem loop miRNA and the closely linked miR-199a miRNAs in PAH. All 4 miRNAs were upregulated in the lung and right ventricle (RV) in mice and rats exposed to the Sugen (SU) 5416 hypoxia model of PAH. Further, expression of the miRNAs was increased in pulmonary artery smooth muscle cells exposed to transforming growth factor β1 but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 56 publications
(94 reference statements)
1
19
0
Order By: Relevance
“…Examination of miR expression in remodeled pulmonary arteries from patients with severe PAH identified miR-126 and miR-21 levels as being upregulated in plexiform compared to concentric lesions while expression of miR-143/145 and miR-204 were higher in concentric lesions [ 25 ]. The role of several miRs, including miR-17-92, miR-143/145, miR-204, miR-214, miR-21, and miR-130/301 in regulating PAH relevant signaling pathways and the disease phenotype has been confirmed in cellular and experimental models of the disease (reviewed in [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]) ( Table 2 ).…”
Section: Micrornas Regulate Gene Expression In Pahmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of miR expression in remodeled pulmonary arteries from patients with severe PAH identified miR-126 and miR-21 levels as being upregulated in plexiform compared to concentric lesions while expression of miR-143/145 and miR-204 were higher in concentric lesions [ 25 ]. The role of several miRs, including miR-17-92, miR-143/145, miR-204, miR-214, miR-21, and miR-130/301 in regulating PAH relevant signaling pathways and the disease phenotype has been confirmed in cellular and experimental models of the disease (reviewed in [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]) ( Table 2 ).…”
Section: Micrornas Regulate Gene Expression In Pahmentioning
confidence: 99%
“…miR-214 is another miR that is upregulated in the lungs and right ventricle (RV) in multiple preclinical models of PAH but, importantly, appears to have sex-related differences in how it modulates the PAH disease phenotype [ 27 , 30 ]. The miR-214 group of miRs includes four distinct mature miRNAs (miR-199-5p, miR-199-3p, miR-214-5p and miR-214-3p) that originate from a bicistronic transcript.…”
Section: Micrornas Regulate Gene Expression In Pahmentioning
confidence: 99%
“…It has been found that miRNA-199a and miRNA-214 are highly expressed in the rat model of PH, which is associated with heart failure caused by pulmonary arterial hypertension. 36) In our final network, miRNA-199b-5p is negatively correlated with HIF1A, and it may act as a negative feedback regulator of HIF1A in CTEPH. The rest of miRNA and lncRNA related to PDGFRB and HIF1A in the final network are not yet reported to be associated with PH or CTEPH.…”
Section: Wang Et Almentioning
confidence: 82%
“…However, based on relevant literature, these networks may also play an important role in other types of PH. 30,31,36) In future, we will also study whether other types of PH have the same results. Secondly, we have not verified the pathways of miRNA-149-5p-PDGFRB-lncRNA CTEPHA1 and miRNA-338-5p/miRNA-199b-5p-HIF1A-lncRNA CTEPHA1 in CTEPH by PCR.…”
Section: Wang Et Almentioning
confidence: 99%
“…; Stevens et al . ; Dai & Zhao, ). Thus, genetically induced alterations in metabolism and signalling in mice when coupled with the end product of PH allow testing of pathways in intact in vivo systems that can then be further evaluated in cell and tissue culture.…”
mentioning
confidence: 99%